Determination of New Reference Force System of 10MN for Build-Up Force Standard Machine at Jilin Institute of Metrology - Qu Zhuo; Lin Hai; Huang Weijun; Ren Xiang (Innovations in Science and Technology Vol. 6, 2022)
This work describes a new reference force system of 10 MN that will be utilised to modernise the Jilin Institute of Metrology’s existing build-up force standard machine. The machine’s history, the concept of modernization, and the function of the new reference force system were all explained. The calibration of this new reference force system was performed several times at NIM, and the long-term stability was investigated using a large amount of test data and results. Meanwhile, the uniformity of two transducer outputs was compared. The distinction between ISO standards and Chinese calibration guidelines is also discussed.